E-portfolios and e-dialogue journals: Exploring their use in teaching writing skills - Titis Dewi Cakrawati; Pangesti Wiedarti (LingTera, 2019)
This research was aimed to find out (1) whether the use of e-portfolios is more effective than the use of e-dialogue journals, (2) whether the use of e-portfolios is more effective than the use of conventional assessments, (3) whether the use of e-dialogue journals is more effective than the use of conventional assessments, and (4) the most effective assessment of all in the teaching of writing skills. This study was a quasi-experimental research using Pretest-Post-test Control Group Design. The data were collected in January-February 2016 in SMK Penerbangan Adisucipto Ardhya Garini. The sample of the research was the students of class X3, X4, and X8 which were determined by using cluster simple random sampling. There were four hypotheses of this study and the research findings revealed that the hypotheses were accepted. It was indicated by all of the Sig values which were lower than the level of significance (0.05).